Letter (copy) : International Brigade Association - Tewson, Vincent
034-0027-001 International. HVT/AC/DT/806. 29th April, 1942. Mr, R.A. Palmer, Co-operative Union Limited, Holyoake House, Hanover Street, Manchester 4. Dear Mr. Palmer, INTERNATIONAL BRIGADE ASSOCIATION. I am attaching herewith copy of a letter which we have received from the Nuneaton Co-operative Society together with copy of our reply. Yours sincerely, Assistant Secretary. Copy of letters. 292/946/34/27